Beyond Income: Religiosity as a Driver of Waqf Intention among Muslim Millennials and Generation Z - Nuradi; Hendri Tanjung; Nurul Huda; Trisiladi Supriyanto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Waqf has emerged as an increasingly important instrument within Islamic social finance due to its potential to promote sustainable social welfare and support long-term socio-economic development. Despite the growing innovation in waqf management and digital philanthropic platforms, participation among Millennials and Generation Z remains relatively limited. This study aims to examine the influence of religiosity on waqf intention and to investigate whether income moderates this relationship among Muslim Millennials and Generation Z in Indonesia. A quantitative cross-sectional survey design was employed, involving 280 valid respondents selected through convenience sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that religiosity has a strong and significant positive effect on waqf intention (β = 0.854, p < .001), confirming that religious commitment is a major driver of Islamic philanthropic behavior among younger Muslims. In contrast, income has no significant direct effect on waqf intention (β = −0.025, p = .435) and does not moderate the relationship between religiosity and waqf intention (β = −0.018, p = .554). The structural model demonstrates substantial explanatory power, accounting for 72.9% of the variance in waqf intention (R² = .729). These findings suggest that waqf intention among Millennials and Generation Z is primarily shaped by internalized religious values rather than economic capacity. The study contributes to the literature on Islamic social finance by highlighting religiosity as an independent motivational driver and provides practical insights for waqf institutions to develop value-based engagement strategies tailored to younger generations.